Xenoestrogens: environmental ubiquity, endocrine disruption, carcinogenic potential, and regulatory challenges - Zdych, Martyna; Cisowska, Zuzanna; Wojciechowska, Zofia; Wiszniowska, Maria; Kucharczyk, Emilia; Gaweł-Dąbrowska, Dagmara (Ecological Questions, 2025)
Xenoestrogens are chemicals that mimic natural estrogens and disrupt hormonal balance, posing health risks such as endocrine disruption and cancer. Recent studies have demonstrated the widespread presence of xenoestrogens in various environmental matrices, encompassing not only pesticides and industrial chemicals but also water, soil, air, and consumer products. Exposure during critical periods such as fetal development and puberty is of particular concern. Increased awareness of the effects of xenoestrogens on hormonal and reproductive health is essential to address their potential long-term health impacts. The presented paper discusses the principal sources of xenoestrogens, elucidating the endocrine mechanisms they activate, and delineating the potential risks associated with neoplastic development.To obtain up-to-date information on trends in xenoestrogens, PubMed and Google Scholar databases, along with the latest legislative reports in Europe and Poland, were reviewed. This study aimed to explore current research on the mechanisms, health impacts, environmental implications, and potential neoplastic threats related to xenoestrogens across diverse ecosystems, with a specific emphasis on their effects on human health and well-being